2020
DOI: 10.1111/jocn.15578
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ perceptions of advance care planning in palliative care unit: a qualitative descriptive study

Abstract: Aims and objectives To describe healthcare professionals’ perceptions of advance care planning (ACP) in palliative care unit in hospital ward or outpatient clinic. Background Clinical guidelines recommend timely ACP as a central component of patient‐centred palliative care. However, the ACP concept and terminology have been judged to be confusing, and practices are not established. Professionals’ views are needed for ACP adoption and usage. Design Qualitative descriptive design. Methods The study used purposiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 37 publications
(116 reference statements)
0
21
0
1
Order By: Relevance
“… 15 , 16 Previous studies have identified knowledge deficit and inexperience as common barriers to good ACP/GoC practice in the acute setting. 17 19 However, since most respondents in our survey were able to identify terminally ill patients with poor life expectancy, it may be argued that knowledge deficit was not a barrier against ACP/GoC. Similarly, skills deficit may also not be a problem since most respondents reported being comfortable with conducting ACP/GoC discussions.…”
Section: Discussionmentioning
confidence: 93%
“… 15 , 16 Previous studies have identified knowledge deficit and inexperience as common barriers to good ACP/GoC practice in the acute setting. 17 19 However, since most respondents in our survey were able to identify terminally ill patients with poor life expectancy, it may be argued that knowledge deficit was not a barrier against ACP/GoC. Similarly, skills deficit may also not be a problem since most respondents reported being comfortable with conducting ACP/GoC discussions.…”
Section: Discussionmentioning
confidence: 93%
“…level of function before the admission, social circumstances), and inexperience as common barriers to good GOC practice in the acute setting. [30][31][32][33] Moreover, there were uncertainties around the impact of this novel virus and risk of rapid deterioration, which meant that there was only a brief window for conversations to occur with patients (when able) and their family. This was complicated further by the imposition of stringent measures to minimise viral transmission risk with intricate visitor restrictions adding layers of complexity in communicating with patients and families.…”
Section: Discussionmentioning
confidence: 99%
“…Boddy et al reported that if healthcare professionals are uncertain about ACP, who is responsible for it, and what and how to talk about it, they may not raise these topics with patients [ 16 ]. Moreover, if healthcare professionals make sufficient preparations, they can better play the role of introducing ACP, so the opinions of healthcare professionals are equally needed, important, and useful [ 17 ]. Their perspectives can reveal existing objective problems about specialization, such as defects in the healthcare system and their urgent need for relevant skills, and thus by examining these problems, the necessary conditions for the long-term development of ACP will also be revealed.…”
Section: Introductionmentioning
confidence: 99%